From stereodynamics to high-throughput screening of catalysed reactions - Stockinger, Skrollan Carina; Gmeiner, Julia Renate; Zawatzky, Kerstin; Troendlin, Johannes; Trapp, Oliver (Chemical communications, 2014)
Characterising chemical reactions by kinetic analysis is of fundamental importance to experimentally obtain insights into reaction mechanisms. Based on such investigations reactions can be optimised and improved catalysts designed. Enhanced reaction conditions may drastically increase the performance of the reaction in terms of yield and (enantio-) selectivity. Understanding reaction kinetics in more complex systems involving adaptive chemical and dynamic systems on a molecular level as shown here is even more challenging. Here we review recent developments in monitoring reactions including the dynamic interconversion of stereoisomers by integrating (catalysed) reactions and chemical analysis in on-column reaction chromatographic devices. These recent developments allow rapid screening of reactions in great detail and are a central tool in determining reaction pathways and to understand how to control the stereodynamics of chiral molecules.